Novel Compensation Method to Reduce Rotor Position Estimation Error and Torque Reduction in Signal Injection Based PMSM Drives - Ravikumar Setty Allampalli; PurnaPrajna R Mangsuli; Kishore Chatterjee (Institute of Advanced Engineering and Science, 2017)
High frequency signal injection techniques are widely used to extract rotor position information from low speed to stand still. Accuracy of estimated rotor position is decreased when stator winding resistance is neglected. Position estimation error also results in output Torque reduction. Parasitic resistance of stator winding causes significant position estimation error and Torque reduction, if not compensated. Signal injection techniques developed in the literature does not provide detailed analysis and compensation methods to improve rotor position estimation of PMS Motors, where stator winding resistance cannot be neglected. This work analyzes the stator winding resistance effect on position estimation accuracy and proposes novel compensation technique to reduce the position estimation error and torque reduction introduced by stator winding resistance. Prototype hardware of a self-sensing PMSM drive is developed. The effectiveness of the proposed method is verified with the MATLAB/Simulink simulations and experimental results on a prototype self-sensing PMSM drive.